Partial fanout multicast switching model of reconfigurable foundation network - Bo ZHANG; Bin-qiang WANG; Sheng-ping ZHU (Tongxin xuebao)
The multicast switching model using copying before scheduling and fanout copying modes had worse large-scale extensibility capability in traditional technology system.A partial fanout multicast switching model with basic switching fabric comprised by 2×2 Boolean cells and Boolean group concentrators was proposed facing to reconfigurable foundation network.Self-routing path selected was realized by partial fanout copying mode and quaternary symbols cut-through coding.Unicast blocking probability,multicast blocking probability and multicast fanout ratio iterative course was deduced based on unicast and multicast mixed business source.The simulation result shows that the value of multicast blocking probability is from 10-10 to 10-2 based on Bernoulli uniform business source when normalized unicast load 0.2,the model can meet time QoS requirement because the value of multicast time delay is less than hundred nano-second level limit.